DFT study on the mechanism of methanol decomposition catalyzed by Mo-CNTs. (December 2020) - Pang, Ke; Ren, Rui-Peng; Lv, Yong-Kang
Abstract: The decomposition of methanol is attracting extensive attention due to the potential broad application prospects of its intermediates. In this work, the decomposition mechanism of methanol has been investigated by calculating the adsorption energy, activation energy and rate constants involved in all elementary reactions of methanol decomposition on Mo-CNTs surface by density functional theory using VASP. There are three possible reaction pathways in methanol initial decomposition, including the cleavage of CO, CH, OH. The activation energies show that the CO and OH bond scission are competitive in methanol initial decomposition. Rate constant analysis determines that the main reaction path is CH3 OH→CH2 OH→CHOH→COH→CO, and the final product is CO. The result shows that carbon deposition was not produced (the activation energy of carbon produced is considerably high). The study provides insight into the methanol decomposition on Mo-CNTs and an effective method to enhance the activity of catalysts.